Saprolegniosis in aquaculture and how to control it? - Lindholm‐Lehto, Petra Camilla; Pylkkö, Päivi (John Wiley & Sons, 2024)
Saprolegniosis, also called water mould, induces a cotton or wool-like white growth on fish skin. It can kill fish at all stages of life, from eggs to adults. It is caused by oomycetes from the genus Saprolegnia and causes fish mortality and huge financial losses to fish farms and hatcheries. Saprolegnia species are endemic and ubiquitous in all freshwater habitats around the world. The exposing factors for saprolegniosis are still largely unknown, but stressors such as temperature shocks, poor water quality, handling and high fish density have been associated with outbreaks. For decades, malachite green was the most effective treatment against Saprolegnia infection, but it has been banned due to its carcinogenic and toxic effects. This has forced farmers to use alternative disinfection methods against Saprolegnia infection, such as hydrogen peroxide, formalin, Bronopol, NaCl, acetic acid and ozone, although many may have safety concerns or are impractical to use. This has led to the investigation of plant-based compounds with antifungal and antibacterial properties against saprolegniosis. These include extracts of certain herbs, onion, garlic, extracts of the plant Chrysanthemum, essential oils of Eryngium campestre, Mentha piperita, Cuminum cyminum and Thymus linearis, which include a variety of phenolic compounds and fatty acids with antifungal properties. This review combines the current knowledge regarding the predisposing factors to Saprolegnia infections and current methods to prevent and treat them, including those under further research. Thus far, many compounds have been tested and studied, but an effective, suitable and safe compound to treat Saprolegnia infection remains to be found.
Keywords: fish pathogen; formalin; hydrogen peroxide; oomycete; plant-based treatments; Saprolegnia parasitica